Professional accreditation of engineering programmes in Russia; World Congress on Engineering and Technology Education, WCETE 2004 (Guarujá/Santos, Brazil, March 14-17, 2004) - Chuchalin A. I. Alexander Ivanovich; Pokholkov Y. P. Yuri Petrovich; Boev O. V.; Mogilnitsky S. B. (2004, 2004)
The paper is devoted to the system of professional accreditation for engineering programmes in addition to the system of higher education institutions (HEI) state accreditation in the Russian Federation. The procedure and criteria for professional accreditation of educational programmes in engineering and technology are presented, as well as the latest activities of the Russian Association for Engineering Education